Growth, yield and economics of maize (Zea mays)-wheat (Triticum aestivum) cropping sequence as influenced by integrated nutrient management - Kumar, Ashok; Gautam, R C; Singh, Ranbir; Rana, K S (The Indian Journal of Agricultural Sciences, 2005)
An experiment was undertaken during 2001-2002 and 2002-03 at IARI, New Delhi to study the effect of integrated nutrient management on the productivity and economics of maize (Zea-mays)-wheat(Triticum aestivum L. emend. Fiori & Paol) cropping sequence. The growth parameters, yield attributes and yield of maize and wheat crops were found the maximum when 100% NPK was applied with farmyard manure @ 10 tonnes/ha. While, the highest net return/rupee invested was recorded with the fertility level of 100% NPK to both the crops. The application of 10 tonnes/ha farmyard manure along with 100% NPK, followed by 100% NPK recorded the highest productivity in terms of maize equivalents of maize-wheat sequence.